THE KNOWLEDGE OF BASIC SURVIVAL SKILLS AMONG PRESCHOOL CHILDREN - Masnan, Abdul Halim; Zulfikri, Aqila Zahirah; Hanafi, Hafizul Fahri (A?f?luna: Journal of Islamic Early Childhood Education, 2020)
This study aims to understand the knowledge of basic survival skill activities among 6 years old children. This study employs qualitative method with case study design in which interview, observation and document analysis are part of the data collection for this study. The samples of the study are 10 children of 6 years old participated in the outdoor survival activities and a teacher is interviewed to support the data of the study. The findings of the study report that there are differences in pre-post-test conducted and the outdoor survival activities are created and adapted in line with the ability and development of 6 years old children. This study implies that children have lack of knowledge about basic survival skills activities and need to be exposed among children. Thus, this study has provided valuable insights into basic survival activities among children in order to help them improve their knowledge skills